The Immune Modulating Properties of Mucosal-Associated Invariant T Cells - Ioannidis, Melina; Cerundolo, Vincenzo; Salio, Mariolina (Frontiers in Immunology, 2020)
Mucosal-associated invariant T (MAIT) cells are unconventional T lymphocytes that express a semi-invariant T cell receptor (TCR) recognizing microbial vitamin B metabolites presented by the highly conserved major histocompatibility complex (MHC) class I like molecule, MR1. The vitamin B metabolites are produced by several commensal and pathogenic bacteria and yeast, but not viruses. Nevertheless, viral infections can trigger MAIT cell activation in a TCR-independent manner, through the release of pro-inflammatory cytokines by antigen-presenting cells (APCs). MAIT cells belong to the innate like T family of cells with a memory phenotype, which allows them to rapidly release Interferon (IFN)-γ, tumor necrosis factor (TNF)-α, and in some circumstances Interleukin (IL)-17 and IL-10, exerting an immunomodulatory role on the ensuing immune response, akin to iNKT cells and γδ T cells. Recent studies implicate MAIT cells in a variety of inflammatory, autoimmune diseases, and in cancer. In addition, through the analysis of the transcriptome of MAIT cells activated in different experimental conditions, an important function in tissue repair and control of immune homeostasis has emerged, shared with other innate-like T cells. In this review, we discuss these recent findings, focussing on the understanding of the molecular mechanisms underpinning MAIT cell activation and effector function in health and disease, which ultimately will aid in clinically harnessing this unique, not donor-restricted cell subtype.